Bertha Estela Benavides - García Barba, Christian (2018)
Excerpt from the interview conducted on February 24, 2016 by Mr. Christian García Barba, Mr. Rodrigo Ramírez Vides and Ms. Daphne Valdivia. Lima Peru.